The emerging roles of macrophages in cancer metastasis and response to chemotherapy. Issue 2 (5th February 2019) - Sanchez, Luis Rivera; Borriello, Lucia; Entenberg, David; Condeelis, John S.; Oktay, Maja H.; Karagiannis, George S.
Abstract: Macrophages represent a heterogeneous group of cells, capable of carrying out distinct functions in a variety of organs and tissues. Even within individual tissues, their functions can vary with location. Tumor‐associated macrophages (TAMs) specialize into three major subtypes that carry out multiple tasks simultaneously. This is especially true in the context of metastasis, where TAMs establish most of the cellular and molecular prerequisites for successful cancer cell dissemination and seeding to the secondary site. Perivascular TAMs operate in the perivascular niche, where they promote tumor angiogenesis and aid in the assembly of intravasation sites called tumor microenvironment of metastasis (TMEM). Streaming TAMs co‐migrate with tumor cells (irrespective of the perivascular niche) and promote matrix remodeling, tumor cell invasiveness, and an immunosuppressive local microenvironment. Premetastatic TAMs are recruited to the premetastatic niche, where they can assist in tumor cell extravasation, seeding, and metastatic colonization. The dynamic interplay between TAMs and tumor cells can also modify the ability of the latter to resist cytotoxic chemotherapy (a phenotype known as environment‐mediated drug resistance) and induce chemotherapy‐mediated pro‐metastatic microenvironmental changes. These observations suggest that future therapeutics should be designed to target TAMs with the aim of suppressing the metastatic potential of tumors and rendering chemotherapy more efficient. Abstract : Review on interplay between tumor‐cells and tumor‐associated macrophages leading to the acquisition of all hallmarks of metastasis